Bearing Capacity of Eccentrically Loaded Strip Footing Near The Edge of Cohesive Slope - Haider S. Al-Jubair; Jawdat K. Abbas (Tikrit Journal of Engineering Sciences, 2007)
The finite element method is used to investigate the behavior of a strip footing constructed near the edge of a sloping cohesive ground. The effects of variation in footing closeness, loading eccentricity and slope angle are studied also. It is proved that Bowles method overestimates the load carrying capacity of the concentrically loaded strip footings on cohesive soils. Decreasing the distance between the footing and the slope edge, increasing the eccentricity and slope angle reduce the ultimate bearing capacity. Slope effect diminishes as the footing distance from the edge approaches (1.5) times its width.